Effect Of Water Content On Characteristics Fuel From The Municipal Solid Waste Through The Pyrolysis Process - Imron Rosyadi; Ni Ketut Caturwati; Ahmad Fauzi (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2020)
The increase in the population of Indonesia is proportional to the increase in the amount of waste produced. Municipal solid waste (MSW) especially organic waste, can be used as solid fuel by means of the torefaction process. Torefaction is a thermo-chemical heat treatment method for biomass conversion that takes place at a temperature of 200oC to 300oC under conditions of atmospheric pressure and in the absence of oxygen. The purpose of this study was to determine the effect of moisture content on calorific, proximate and ultimate values ​​of torefaction samples using municipal solid waste. Setting the water content in the mixed sample (30% rice + 70% wood) with variations in moisture content of 30%, 40%, and 50%; and rice and wood samples with variations in moisture content of 40% and 50%. The torefaction was carried out at a temperature of 300oC for one hour and inert gas N2. Torefaction products have been tested contain of the calorific value, proximate testing, and ultimate testing. The results obtained were the best calorific value in the rice sample, the moisture content of 40% was 6351.1 cal / g or equivalent to sub-bituminous coal. The proximate and ultimate results of the best heating value are rice samples with 40% moisture content, fixed carbon 62.95%, volatile matter 27.85%, moisture 7.06%, ash 2.14%, carbon 71.85%, hydrogen. 2.80%, nitrogen 3.17%, and sulfur 0.05%. The calorific value calculation method that is almost close to the test results is the Dulong method, with an average error percentage of 1.63%.